Weaponization of interdependence in international relations: economic and political sanctions in world politics - Kachan, O. ("M. Narikbayev KAZGUU University". Nur-Sultan, 2020)
A new era of globalization is marked by the sharp increase in the number of sanctions, which serve as a standard policy instrument used by nations and international organizations to address any actions of a target state that the sender state or group of states disagreed with. The present master thesis studies the restrictive measures imposed by the United States and the European Union on the Russian Federation as it is one of the most prolonged sanctions regime in the modern history. The study attempts to analyse and understand how and why these sanctions are implemented. In particular, the interest of the present master thesis is not in every aspect of sanctions but only in the justification of their imposition. Thus, the purpose of this research is to explore the arguments provided for justification of sanctions in international politics using the example of the Russian Federation. The present study is primarily a desktop research in which the analysis is based on a review of literature, international reports, interviews of the leaders, economic and financial data from international organisations, and various online resources. The results of the descriptive and interpretive analysis of the data revealed that the actions undertaken by every actor are justifiable. Still, it is hard to say whose arguments are more convincing.